2013
DOI: 10.1038/nm.3100
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of T cell repertoire recovery after hematopoietic stem cell transplantation

Abstract: Delayed T-cell recovery and restricted T-cell receptor (TCR) diversity after allogeneic hematopoietic stem cell transplantation (allo-HSCT) are associated with increased risks of infection and cancer relapse. Technical challenges have limited faithful measurement of TCR diversity following allo-HSCT. Here we combined 5′-RACE PCR with deep sequencing, to quantify TCR diversity in 28 allo-HSCT recipients using a single oligonucleotide pair. Analysis of duplicate blood samples confirmed that the frequency of indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
167
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(184 citation statements)
references
References 39 publications
14
167
3
Order By: Relevance
“…Van Heijst and colleagues report consistent findings of patient groups with increased TCR diversity and decreased risk of infection and cancer relapse. 32 In patients following septic shock, TCR diversity is reduced and normalization of TCR diversity and PD-1 expression was reported to positively correlate with survival. 33 In patients with hepatitis C virus (HCV) infection, Miles and colleagues observed that TCR repertoire diversity is associated with HCV clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Van Heijst and colleagues report consistent findings of patient groups with increased TCR diversity and decreased risk of infection and cancer relapse. 32 In patients following septic shock, TCR diversity is reduced and normalization of TCR diversity and PD-1 expression was reported to positively correlate with survival. 33 In patients with hepatitis C virus (HCV) infection, Miles and colleagues observed that TCR repertoire diversity is associated with HCV clearance.…”
Section: Discussionmentioning
confidence: 99%
“…DUCB recipients had a lower incidence of infection, higher CD4 C T cell numbers and a reduced rate of leukemia relapse compared with TCD recipients. 8 Muraro et al reported that CD4 C T and CD8 C T TCR diversity in response patients was increased compared with non-response patients before and after haematopoietic stem cell transplantation. 9 Jia et al reported that high NSDE of the mucosal T cell repertoire in gastric cancer correlates with patient short-term and overall survival time.…”
Section: Discussionmentioning
confidence: 99%
“…7 TCR diversity is closely related to treatment effectiveness and patient prognosis in different diseases. [8][9][10][11] The analysis of TCR diversity in diseases might also facilitate the elucidation of pathogenesis and the development of cellular immunotherapy approaches that target specific tumors and neoantigens. 12,13 Although tumor-infiltrating T lymphocytes have implications for tumor prognosis, information on the TCR diversity of HBV-associated liver cancer remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…37,38 Briefly, total RNA was extracted and TRB gene products were amplified through 5' rapid amplification of cDNA ends (RACE) PCR (Clontech, Palo Alto, CA, USA) followed by sequencing with Roche 454 sequencer (Roche, Basel, Switzerland).…”
Section: Pcr Specific For the Tcrmentioning
confidence: 99%